2023
DOI: 10.1021/acs.inorgchem.3c01842
|View full text |Cite
|
Sign up to set email alerts
|

Divalent Heterometal Doped Titanium-Oxide Cluster Polymers: Structures, Photoresponse, and Photocatalysis

Abstract: Five cluster polymers based on heterometal-doped titaniumoxide cluster (TOC) monomers are reported. The monomers feature Ti 10 -oxide cluster cores and are connected to the divalent closed-shell heterometal anchors by salicylate ligands. The Sr 2+ , Ba 2+ , and Pb 2+ dopants cause the monomers to bind head-to-head and generate linear chains, while the Ca 2+ and Cd 2+ lead to head-to-tail connections and zigzag chains. The cluster polymers are responsive to visible-light up to 565 nm and photo-catalytically act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…To investigate the roles of the active species responsible for RhB degradation, the effects of ascorbic acid (AA, an h + quencher), ispropanol (HO i Pr, an ˙OH quencher), superoxide dismutase (SOD, an O 2 ˙ − quencher), 1,4-diazabicyclo[2.2.2]-octane (DABCO, a 1 O 2 quencher) on the photocatalytic degradation of RhB were investigated. 43–45 For the Ti 12 Pb 2 system, AA and HO i Pr substantially retarded the degradation, while DABCO and SOD had no effect. Therefore, h + and O 2 ˙ − were the active species.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…To investigate the roles of the active species responsible for RhB degradation, the effects of ascorbic acid (AA, an h + quencher), ispropanol (HO i Pr, an ˙OH quencher), superoxide dismutase (SOD, an O 2 ˙ − quencher), 1,4-diazabicyclo[2.2.2]-octane (DABCO, a 1 O 2 quencher) on the photocatalytic degradation of RhB were investigated. 43–45 For the Ti 12 Pb 2 system, AA and HO i Pr substantially retarded the degradation, while DABCO and SOD had no effect. Therefore, h + and O 2 ˙ − were the active species.…”
Section: Resultsmentioning
confidence: 98%
“…The photocatalytic degradation of dyes is typically used for evaluating the potential of photocatalysts in water remediation. 36,41–43 Here, Ti 12 Pb 2 and Ti 14 were used in the degradation of a representative dye pollutant, rhodamine B. 13,44 The adsorption/desorption experiments in the dark revealed that both clusters hardly adsorbed RhB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They allow researchers to construct atomic structure models that are specifically designed to enhance the performance of solar cells. Innovative structural design strategies, demonstrate the potential of metal clusters in optimizing the efficiency and stability of solar cells [130] . Metal‐cluster sensitized solar cells utilize metal clusters as photosensitizers to enhance the light absorption and charge separation capacity of solar cells.…”
Section: Discussionmentioning
confidence: 99%
“…Innovative structural design strategies, demonstrate the potential of metal clusters in optimizing the efficiency and stability of solar cells. [130] Metalcluster sensitized solar cells utilize metal clusters as photosensitizers to enhance the light absorption and charge separation capacity of solar cells. This results in an improvement in the efficiency and performance of the solar cells.…”
Section: Discussionmentioning
confidence: 99%